Challenges in Quality of Education in Higher Education Institutions (HEIs) of Pakistan - Sain, Zohaib Hassan (International Conference on Sciences Development and Technology, 2022)
The purpose of this study is based on exploratory research to identify “Challenges in Quality of Education in HEIs of Pakistan”. Exploratory research approach is used to achieve the objectives of the study in less time and inexpensive means. From the last few years, Pakistan is facing a lot of challenges in education sector such as curriculum, less training institutions, corruption in education, teacher’s behavior, less research work. Emerging issues in education sector are less training institutions and trend towards research work which is essential to follow for the growth and strength of any economy. The purpose of our research is to identify the major challenges in educational sector in Pakistan which the educational sector is suffering from last few years. The researcher used triangulation in order to carry the reliability and validity of the data for results. So, to conduct this triangulation the researcher used survey poll for the students, questionnaire for the teachers and interviews of the management. . In this regard primary data was collected from the focused group of students using a sample of 100 questionnaires for each university were filled by the students of the selected five universities. This attempt of conducting the research will play an important role in the development of Pakistan. In this research Curriculum, Corruption in education, less training institutions, Teacher’s behavior and less research work are independent variables and Quality of Education is dependent variable. In future, we will research on the solution of these problems. To increase the literacy rate, the Govt. of Pakistan has announced that the education is compulsory for sixteen years old for every citizen.